Coping with methods for delineating emerging fields: Nanoscience and nanotechnology as a case study - Muñoz-Écija, Teresa; Vargas-Quesada, Benjamín; Chinchilla Rodríguez, Zaida (Journal of informetrics, 2019)
•We use, compare and discuss different approaches for delineating emerging fields taking nanoscience and nanotechnology as a case study.•A conceptual framework for employing three distinct approaches is proposed.•Comparison of the approaches —at subject category, journal and publication level— yield quite different results.•Field delineation shows certain problems at the quantitative and qualitative level, especially for interdisciplinary fields. Proper field delineation plays an important role in scientometric studies, although it is a tough task. Based on an emerging and interdisciplinary field nanoscience and nanotechnology– this paper highlights the problem of field delineation. First we review the related literature. Then, three different approaches to delineate a field of knowledge were applied at three different levels of aggregation: subject category, publication level, and journal level. Expert opinion interviews served to assess the data, and precision and recall of each approach were calculated for comparison. Our findings confirm that field delineation is a complicated issue at both the quantitative and the qualitative level, even when experts validate results.